P-018 Curative transvenous embolization of craniofacial arteriovenous malformation. (16th November 2010) - Feng, L; Mattson-Gates, G; Sosa, V; Baker, C
Abstract : Background: Craniofacial arteriovenous malformation (AVM) is a challenging disease to eradicate, often requiring the combination of embolization and reconstructive surgery. The tortuosity of distal feeding arteries and the presence of abundant collaterals make it difficult to obliterate the nidus with transarterial embolization. In this small case series, we report curative transvenous embolization of craniofacial AVM under transient arrest of arterial inflow. Materials and methods: Four patients with craniofacial AVMs (two in the scalp, one in the face and one in the forehead) were embolized transvenously with Onyx. In all cases, the dominant feeding arteries were first embolized with Onyx to reduce arterial inflow. The major draining veins were then accessed transfemorally or via direct puncture. Detachable coils were placed in the venous pouches to further obstruct outflow from the AVM nidus. After arterial inflow was completely stopped with the placement of a tourniquet on the head or inflation of a balloon catheter in the external carotid artery, we injected Onyx into the venous pouch to retrogradely fill the entire AVM nidus. Follow-up angiograms were performed 1 year later. Results: Angiographic cure was achieved in all four patients. The mass effect from the Onyx cast was not disfiguring. No patient had skin necrosis or a visible black mark on the skin. The first two patients underwent surgical removal of the Onyx cast which was scheduled before embolization. The next two patients declined surgery because they were not bothered by the Onyx cast. No recurrence was found at the 1 year follow-up angiogram. Conclusion: Head and neck AVM can be safely cured with transvenous embolization using Onyx. Abstract P-018 Figure 1 Angiogram of a facial arteriovenous malformation before and after embolization. Abstract P-018 Figure 2 Transvenous embolization with Onyx after partial coiling and transient occlusion of the external carotid artery with a balloon (A). Onyx cast showing the nidus and numerous small feeders (B).